How exposure to ALS-inhibiting gametocide tribenuron-methyl induces male sterility in rapeseed - Jing-long Lian; Li-Suo Ren; Cong Zhang; Cheng-Yu Yu; Zhen Huang; Ai-Xia Xu; Jun-Gang Dong (BMC Plant Biology, 2019)
Abstract Background Acetolactate synthase (ALS)-inhibiting herbicide tribenuron-methyl (TBM) is an efficient gametocide that can cause rapeseed (Brassica napus L.) to become male sterile and outcrossing. To find the reason the TBM treatment leads to male sterility, an integrated study using cytological, physiological, and transcriptomic methods was conducted. Results Some temporary symptoms, including the discoloration of young leaves and a short halt of raceme elongation, were observed in the rapeseed plants exposed to TBM at an application rate of 1 μg per plant. Both chloroplasts in young leaves and plastids in anthers were deformed. TBM also reduced the leaf photosynthetic rate and the contents of chlorophyll, soluble sugar and pyruvate. Both the tapetal cells and uni-nucleate microspores in the treated plants showed large autophagic vacuoles, and the tissue degenerated quickly. A transcriptomic comparison with the control identified 200 upregulated and 163 downregulated differential expression genes in the small flower buds of the TBM treatment. The genes encoding functionally important proteins, including glucan endo-1,3-beta-glucosidase A6, QUARTET3 (QRT3), ARABIDOPSIS ANTHER 7 (ATA7), non-specific lipid-transfer protein LTP11 and LTP12, histone-lysine N-methyltransferase ATXR6, spermidine coumaroyl-CoA acyltransferase (SCT), and photosystem II reaction centre protein psbB, were downregulated by TBM exposure. Some important genes encoding autophagy-related protein ATG8a and metabolic detoxification related proteins, including DTX1, DTX6, DTX35, cytosolic sulfotransferase SOT12, and six members of glutathione S-transferase, were upregulated. In addition, several genes related to hormone stimulus, such as 1-aminocyclopropane-1-carboxylate synthase 8 (ACS8), ethylene-responsive factor ERF1A, ERF1, ERF71, CRF6, and RAP2-3, were also upregulated. The transcriptional regulation is in accordance with the functional abnormalities of pollen wall formation, lipid metabolism, chloroplast structure, ethylene generation, cell cycle, and tissue autophagy. Conclusion The results suggested that except for ALS, the metabolic pathways related to lipid metabolism, pollen exine formation, photosynthesis and hormone response are associated with male sterility induced by TBM. The results provide new insight into the molecular mechanisms of inducing male sterility by sulfonylurea.